Analyzing the justifications for the proposal to lower the age of criminal majority - Sandrini Mansur, Thiago; Edinete (Argumentum, 2021)
This paper examines the justifications behind proposals to lower the age of criminal majority, assessing their integrity against the principal scientific findings. We searched the virtual pages of the Chamber of Deputies and the Federal Senate and their respective official journals. The corpus consisted of 59 Proposals to Amend the Constitution, which we subjected to thematic content analysis. The justifications dealt with five themes, named according to their main ideas: “maturity, conscience and discernment”; "impunity"; "insecurity"; “Media and public opinion”; and “judicial grounds”. National and international evidence contradicts the justifications presented by these parliamentarians, leading us to conclude that lowering the age of criminal majority lacks any theoretical and empirical foundation.